GEO-TOURISM OPPORTUNITY DEVELOPMENT ON KAMOJANG FOREST IN WEST JAVA - Gunardi Djoko Winarno; Ikhwan Muslih; Indra Gumay Febryano; Arief Darmawan; Dian Iswandaru; Trio Santoso (Jurnal Belantara, 2023)
The landscape of volcanic and geothermal energy which has an attractive object and unique ecotourism is very important for geo-tourism destination. Nevertheless the use of geothermal so far in Indonesia including Kawah Kamojang only for electricity production which is still not optimal, but it has the potential of tourism in the form of craters geothermal and other potential tourist activity. The research is needed to discuss the spectrum of tourism opportunities in Kawah Kamojang forest. The method for this study is Recreation Opportunity Spectrum (ROS), which was developed by the U.S. Forest Service. The result is a spectrum of geothermal potential ecotourism developed in integrated 6 ecotourism sites such as Geothermal Installation, TWA Kawah Kamojang, Situ Ciharus, Situ Cibeureum, Tourism Village, and Eagle Conservation Center. Some programs and tourism activities may be able to be potentially developed such as camping, jungle trekking, hiking, swimming, fishing, flora and fauna sighting, hot water bath, educational, culinary and cultural tourism. The constraints on developing geotourism are facilities and services, management, social and collision with applicable regulations. Therefore, there should be a joint effort and collective work between central government, local government, private sector, NGOs, educational institutions/ universities, and local communities towards this plan.